What is documentation doing? Early childhood education teachers shifting from and between the meanings and actions of documentation practices. (June 2021) - Albin-Clark, Jo
This article asks the question of what documentation is doing, rather than what documentation means in the context of early childhood education. By focusing on the documentation of a young child's playful exploration with water that inhabits a classroom wall, new materialist theories are put to work to ponder documentation's agentive capacities and intra-activities. What is argued is that documentation is inviting powerful creating and resisting actions that offer senses of belonging for a child. Consequently, it is proposed that teachers both shift from and overlay matters of fact and matters of concern. The implication is that documentation can be put to work in influential ways when its actions (rather than meanings) within spaces are foregrounded. This article offers original contributions to contemporary debates regarding agentive readings of documentation practices that can influence forms of ethical and flourishing pedagogies in a policy climate that can otherwise confine.